Genetic susceptibility to enteric fever in experimentally challenged human volunteers - Barton, A; Hill, J; Bibi, S; Chen, L; Jones, C; Jones, E; Camara, S; Shrestha, S; Jin, C; Gibani, MM; Dobinson, H; Waddington, C; et al. (American Society for Microbiology, 2022)
Infections with Salmonella enterica serovars Typhi and Paratyphi A cause an estimated 14 million cases of enteric fever annually. Here, the controlled nature of challenge studies is exploited to identify genetic variants associated with enteric fever susceptibility. Human challenge participants were genotyped by Illumina OmniExpress-24 BeadChip array (n = 176) and/or transcriptionally profiled by RNA sequencing (n = 174). While the study was underpowered to detect any single nucleotide polymorphisms (SNPs) significant at the whole-genome level, two SNPs within CAPN14 and MIATNB were identified with P < 10−5 for association with development of symptoms or bacteremia following oral S. Typhi or S. Paratyphi A challenge. Imputation of classical human leukocyte antigen (HLA) types from genomic and transcriptomic data identified HLA-B*27:05, previously associated with nontyphoidal Salmonella-induced reactive arthritis, as the HLA type most strongly associated with enteric fever susceptibility (P = 0.011). Gene sets relating to the unfolded protein response/heat shock and endoplasmic reticulum-associated protein degradation were overrepresented in HLA-B*27:05+ participants following challenge. Furthermore, intracellular replication of S. Typhi is higher in C1R cells transfected with HLA-B*27:05 (P = 0.02). These data suggest that activation of the unfolded protein response by HLA-B*27:05 misfolding may create an intracellular environment conducive to S. Typhi replication, increasing susceptibility to enteric fever.